Estimation of the window period of human T‐cell leukemia virus type 1 and 2 tests by a lookback study of seroconverters among Japanese voluntary blood donors. Issue 2 (24th December 2020) - Sagara, Yasuko; Nakamura, Hitomi; Yamamoto, Midori; Ezaki, Toshinobu; Koga, Tomohide; Shimamura, Masuhiro; Satake, Masahiro; Irita, Kazuo
Abstract: Background: Japan is endemic for human T‐cell leukemia virus type 1 (HTLV‐1), and the horizontal transmission of HTLV‐1 is often reported. However, the window period (WP) for serologic or molecular screening is unclear. Study Design and Methods: Results for anti–HTLV‐1 screening and confirmatory tests obtained from 648 591 repeated blood donors in the Kyushu district, one of the most endemic areas of HTLV‐1 in the world, were evaluated. A lookback study was conducted for seroconverters. Results: During 2012 to 2019, 436 seroconverters (155 men, 281women) were identified with use of a screening chemiluminescence enzyme‐immunoassay (CLEIA) and multiple confirmatory tests. Because the period between the latest seronegative donation and seroconversion was highly variable (2.1‐276.7 months), 19 cases that seroconverted within 6 months were subjected to the analysis. The WP of the particle agglutination assay and CLEIA was estimated to be 2.2 ± 0.6 and 2.6 ± 1.7 months, respectively. The WP of the indirect immunofluorescence assay was 4.8 ± 6.5 months. Although the WP of western blotting was estimated to be 6.3 ± 8.7 months, four cases were still indeterminate through the study period. Chemiluminescence and line immunoassays, the current screening and confirmatory tests used in the Japanese blood program, showed the shortest WP of 2.2 ± 0.6 months. The WP of real‐time polymerase chain reaction for HTLV‐1 was estimated to be 4.1 ± 7.8 months. Conclusions: The WP in commercially available testing systems for HTLV‐1/2 was determined for natural infection among repeated blood donors. Considering the HTLV‐1 WP will help increase transfusion safety and facilitate the accurate diagnosis of HTLV‐1 infection.